2022
DOI: 10.3390/min12121619
|View full text |Cite
|
Sign up to set email alerts
|

Are Coal-Hosted Gallium-Rich Ores Elastically Detectable: A Rock-Physics Modeling Perspective

Abstract: Coal-hosted gallium-rich ores are mainly explored with geochemical analyses, and their elasticities lack research. This paper incorporated core testing, rock-physics modeling, and Monte Carlo simulations to characterize the elastic parameters of gallium-rich cores and discuss whether coal-hosted gallium-rich ores are elastically detectable. The measured cores from No. 6 coal in the Heidaigou mine showed that the gallium contents strongly correlate to the boehmite contents with a 0.96 correlation coefficient. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…The Haerwusu mine stands as a significant producer within the Jungar coalfield, situated on the northeast margin of the Ordos basin in North China (see Figure 1). With a mining area spanning 61.4 km 2 and a coal reserve estimated at 1.73 billion tons, it holds substantial importance [4,24]. The primary coal-bearing formations in the mine consist of the Carboniferous Taiyuan and lower Permian Shanxi formations.…”
Section: Geological Setting and Core Sampling 21 Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The Haerwusu mine stands as a significant producer within the Jungar coalfield, situated on the northeast margin of the Ordos basin in North China (see Figure 1). With a mining area spanning 61.4 km 2 and a coal reserve estimated at 1.73 billion tons, it holds substantial importance [4,24]. The primary coal-bearing formations in the mine consist of the Carboniferous Taiyuan and lower Permian Shanxi formations.…”
Section: Geological Setting and Core Sampling 21 Geological Settingmentioning
confidence: 99%
“…The elastic parameters commonly discussed include bulk and shear moduli, P-and S-wave impedances and velocities, quality factor Q, Poisson ′ s ratio, and anisotropy parameters. In the coal industry, pioneers have utilized rock physics modeling to delineate coal-rank-related velocities and anisotropies, bulk moduli associated with absorbed methane, and variations in velocities and moduli related to gallium content [24][25][26][27]. Additionally, rock physics modeling has been employed to construct interpretation templates for oil and gas reservoirs as well as coal-hosted gallium deposits [24,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction and utilization of critical elements from coal and coal ash seems to be an alternative for sourcing critical metals [56]. Literature sources have already demonstrated that critical elements such as uranium, germanium, REEs, yttrium, gallium, and aluminum can be extracted from coal combustions products [56][57][58]. More research should be performed on finding highly elevated concentrations of critical elements in metals, and the efficient extraction technology should be optimized.…”
Section: Co-occurrence Keyword Networkmentioning
confidence: 99%
“…Despite this advantage, very few studies have utilized DEM to investigate this phenomenon, essential to comprehend the mechanical behavior of natural and engineered composite granular materials. A common practice among the geoscientists working in the field of rock physics is that the effective dry modulus is constrained by Voigt-Reuss bounds and Hashin-Shtrikman bounds and is calculated using the Voigt-Reuss-Hill average (Ali et al 2020;Dou et al 2011;Chen and Song 2022;Pan et al 2020;Stefaniuk and Kachanov 2023). However, very little attention is paid to the micro-structural geometrical configuration of minerals within the assemblage or the arching effects observed in granular materials.…”
Section: Introductionmentioning
confidence: 99%